An Oxygen Vacancy Memristor Ruled by Electron Correlations. Issue 27 (28th July 2022) - Humbert, Vincent; El Hage, Ralph; Krieger, Guillaume; Sanchez‐Santolino, Gabriel; Sander, Anke; Collin, Sophie; Trastoy, Juan; Briatico, Javier; Santamaria, Jacobo; Preziosi, Daniele; Villegas, Javier E.
Abstract: Resistive switching effects offer new opportunities in the field of conventional memories as well as in the booming area of neuromorphic computing. Here the authors demonstrate memristive switching effects produced by a redox‐driven oxygen exchange in tunnel junctions based on NdNiO3, a strongly correlated electron system characterized by the presence of a metal‐to‐insulator transition (MIT). Strikingly, a strong interplay exists between the MIT and the redox mechanism, which on the one hand modifies the MIT itself, and on the other hand radically affects the tunnel resistance switching and the resistance states' lifetime. That results in a very unique temperature behavior and endows the junctions with multiple degrees of freedom. The obtained results bring up fundamental questions on the interplay between electronic correlations and the creation and mobility of oxygen vacancies in nickelates, opening a new avenue toward mimicking neuromorphic functions by exploiting the electric‐field control of correlated states. Abstract : A reversible oxygen exchange at the interface between an amorphous metal (Mo80 Si20 ) and a strongly correlated oxide (NdNiO3, NNO) yields strong resistive switching effects. Interestingly the metal‐to‐insulator transition characteristic of NNO interplays with that redox mechanism, leading to a very unique behavior that opens new avenues for mimicking neuromorphic functions by exploiting the electric‐field control of correlated states.